Dual sgRNA-directed knock out survivin gene expression using CRISPR/Cas9 technology for editing survivin gene in triple-negative breast cancer - Syahrani, Resda A.; Wanandi, Septelia I.; Arumsari, Sekar; Nihayah, Silviatun; Watanabe, Yukihide; Mizuno, Seiya; Louisa, Melva; Wuyung, Puspita E. (Narra J, 2024)
Clustered regularly interspaced short palindromic repeats (CRISPR)-associated nuclease 9 (CRISPR/Cas9) offers a robust approach for genome manipulation, particularly in cancer therapy. Given its high expression in triple-negative breast cancer (TNBC), targeting survivin with CRISPR/Cas9 holds promise as a therapeutic strategy. The aim of this study was to design specific single guide ribonucleic acid (sgRNA) for CRISPR/Cas9 to permanently knock out the survivin gene, exploring its potential as a therapeutic approach in breast cancer while addressing potential off-target effects. Survivin gene knockout was conducted in the TNBC cell line BT549. Intron 1, exon 2, and intron 2 of the survivin gene were selected as sgRNA targets. These sgRNAs were designed in silico and then cloned into a CRISPR/Cas9 expression plasmid. The cleavage activity was assessed using an enhanced green fluorescent protein (EGFP) expression plasmid. The sgRNAs with higher cleavage activity were selected for the establishment of knockout cells. After transfecting the plasmid into the cells, the success of the survivin gene knockout was validated at the deoxyribonucleic acid (DNA) level using polymerase chain reaction (PCR) and sequencing analysis, and at the protein expression level using Western blotting. The study found that sgRNAs survin1A (targeting intron 1), survex2A (targeting intron 2), and survin2A (targeting intron 2) demonstrated higher cleavage activities compared to the other sgRNAs. However, using the single sgRNA, survex2A did not generate mutations in the survivin gene. At the protein level, survivin was still expressed, indicating that a single sgRNA was ineffective in knocking out the survivin gene. In contrast, the combination of sgRNA survin1A and sgRNA survin2A was more effective in generating mutations in the survivin gene, resulting in the deletion of the entire exon 2 and leading to a loss of survivin protein expression. In conclusion, our work provides specific sgRNAs and demonstrates the utilization of dual sgRNAs strategy in the CRISPR/Cas9 technology to knock out the survivin gene, showing potential in breast cancer therapy.